2017
DOI: 10.11648/j.ajbio.20170505.12
|View full text |Cite
|
Sign up to set email alerts
|

Community Knowledge, Attitude and Practice About Malaria and Mosquito Biting Behavior in Southern Ethiopia

Abstract: Malaria has been the leading cause of mortality for many years in underdeveloped countries like Ethiopia.Community Knowledge of cause and transmission of malaria and mosquito feeding behavior is key to design appropriate health communication strategies for malaria prevention and control. The present study aimed to assess knowledge and awareness on malaria and its association with mosquitoes in Dembele kebele, southeastern, Ethiopia. A community cross sectional study was carried out in Dembele kebele from Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
3
7
1
Order By: Relevance
“…The details of the result showed that male patients were less likely to possess good attitudes on uncomplicated malaria and its management compared to females. Moreover, although the effects on knowledge and practices were insignificant (Table VI), they were in agreement with previous studies conducted in the southern part of Nigeria which indicated the likelihood of females taking better care of their health than their male counterparts [38]; this, however, contrasted with another study conducted in Ethiopia and India, which reported males were more likely to be knowledgeable than females [39, 40]. The positive influence of age on respondents' knowledge on the disease and its management agreed with other studies conducted among community members in Ethiopia which reported age as a factor that influenced respondents' knowledge on malaria and on mosquito-biting behaviours [40].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The details of the result showed that male patients were less likely to possess good attitudes on uncomplicated malaria and its management compared to females. Moreover, although the effects on knowledge and practices were insignificant (Table VI), they were in agreement with previous studies conducted in the southern part of Nigeria which indicated the likelihood of females taking better care of their health than their male counterparts [38]; this, however, contrasted with another study conducted in Ethiopia and India, which reported males were more likely to be knowledgeable than females [39, 40]. The positive influence of age on respondents' knowledge on the disease and its management agreed with other studies conducted among community members in Ethiopia which reported age as a factor that influenced respondents' knowledge on malaria and on mosquito-biting behaviours [40].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, although the effects on knowledge and practices were insignificant (Table VI), they were in agreement with previous studies conducted in the southern part of Nigeria which indicated the likelihood of females taking better care of their health than their male counterparts [38]; this, however, contrasted with another study conducted in Ethiopia and India, which reported males were more likely to be knowledgeable than females [39, 40]. The positive influence of age on respondents' knowledge on the disease and its management agreed with other studies conducted among community members in Ethiopia which reported age as a factor that influenced respondents' knowledge on malaria and on mosquito-biting behaviours [40]. The education level of the respondents was also a predictor of their knowledge on the disease and its management, and this was consistent with previous studies [40, 41], but in contrast with reports of Das and Ravindran [39].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The required sample size was calculated using single population proportion formula;n = (Zα/2) 2 p(1-p)//d 2 where; n is the required sample size, Z a/2 is the value of standard score at 95% confidence interval, p is the expected proportion of knowledge, and d 2 is marginal error. And the following assumptions were used inorder to calculate the required sample size; 17.7% population proportion of malaria knowledge [25], 95% confidence interval, marginal error of 5% and 5% non-response rate. So the final sample size was 236 and those sampled participants were selected by systematic sampling technique.…”
Section: Methodsmentioning
confidence: 99%
“…Cross-sectional studies were done in Ethiopia especially in Shahsango [24], Bonke [25], and Tepi [26] to assess knowledge on malaria among pregnant women showed that 74.1%, 16.5%and 17.7% of the respondents had good knowledge respectively. However; different studies reveal that practice of malaria preventive measure and health-seeking behavior of the community are related to the level of knowledge.…”
Section: Introductionmentioning
confidence: 99%